Fatwa Communication Literacy Related to The Law of Boycotting Pro-Israel Product Transactions in Indonesia - Islamy, Athoillah; Ubaidillah, Ubaidillah; Ariyadi, Ariyadi; Abduh, Muhammad (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
The movement to boycott pro-Israel products as a form of condemnation of Israel's aggression against Palestine demands the attention of all elements of society, government and religious leaders in various countries, including in Indonesia. This qualitative study with a content analysis approach aims to identify the construction of mass communication functions in the fatwa of the Majelis Ulama Indonesia (MUI) Number 83 of 2023 related to the boycott of pro-Israel products. The mass communication function theory constructed by Harold Lasswell became the foundation of the perspective. This study found the construction of mass communication functions in the MUI's fatwa literacy related to the boycott of pro-Israel products, including the function of environmental monitoring related to various events, such as Israeli aggression against Palestine which received financial assistance from various pro-Israel companies, and public questions from Muslims regarding the law of supporting the Palestinian cause. Then, the function of social correlation, such as the appeal for Muslims to do philanthropy for humanitarian solidarity for the struggle of the Palestinian people, and avoid using various pro-Israel products. Furthermore, the function of social transmission is in the form of MUI's role in disseminating Islamic legal norms that can guide Muslims in responding to the boycott movement of Israeli products. This study confirms the importance of constructing a holistic mass communication function involving the synergy of the roles of the community, religious leaders, and the government in disseminating fatwa literacy related to social religious problems, such as the fatwa related to the boycott of pro-Israel products. The focus, perspective and implications of the findings of this study are also novelty to the findings of previous studies which generally focus more on the formal legal aspects related to fatwas related to the boycott of pro-Israel products. However, this study does not examine the economic impact on Muslims in Indonesia of the MUI fatwa related to the boycott.